2020
DOI: 10.1093/ajcp/aqaa097
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation and Utilization of Multiple Molecular In Vitro Diagnostic Assays for the Detection of SARS-CoV-2

Abstract: Abstract Objectives To evaluate the clinical performance of 3 molecular assays for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Methods We used 184 nasopharyngeal swab specimens to compare Abbott ID NOW COVID-19 (Abbott ID NOW), DiaSorin Molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 13 publications
5
60
0
Order By: Relevance
“… 43 Altogether the 51 studies analyzed 18,923 persons, of them 10,181 persons (22 studies) before COVID-19 and 8,742 persons for SARS-CoV-2 (29 studies). 7 , 9 , 13 , 14 , 17 , 18 , 19 , 22 , 23 , 25 , 26 , 27 , 34 , 35 , 36 , 38 , 39 , 41 , 43 , 45 , 46 , 47 , 50 , 51 , 53 , 54 , 55 , 56 The studies evaluated mostly patients with non-specific ILI or suspected COVID-19, the latter including both upper ARTI and pneumonia. Five studies included only children <2 years 16 , 21 , 31 , 32 , 48 , 25 studies included a mixed age range and 21 did not address patients' age.…”
Section: Resultsmentioning
confidence: 99%
“… 43 Altogether the 51 studies analyzed 18,923 persons, of them 10,181 persons (22 studies) before COVID-19 and 8,742 persons for SARS-CoV-2 (29 studies). 7 , 9 , 13 , 14 , 17 , 18 , 19 , 22 , 23 , 25 , 26 , 27 , 34 , 35 , 36 , 38 , 39 , 41 , 43 , 45 , 46 , 47 , 50 , 51 , 53 , 54 , 55 , 56 The studies evaluated mostly patients with non-specific ILI or suspected COVID-19, the latter including both upper ARTI and pneumonia. Five studies included only children <2 years 16 , 21 , 31 , 32 , 48 , 25 studies included a mixed age range and 21 did not address patients' age.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies determined the accuracy or agreement of rRT-PCR or automated rRT-PCR platforms/instruments compared to a reference standard based on the results of several tests as a "composite reference standard" ( Table 3 ). [18][19][20] There were between 58 and 184 patients per study. Suo et al considered a positive result of either repeated measurements of rRT-PCR or serology to indicate a positive test according to the reference standard; reported sensitivity of initial rRT-PCR result was 40%, rSp 100%, rPPV 100%, and rNPV 16%.…”
Section: The Performance Of Rrt-pcr Compared To Various Composite Refmentioning
confidence: 99%
“…While Abbott ID NOW had a rPPA of 91%, the Roche cobas 6800 and Diasorin Simplexa assays had a rPPA of 100%. 18 These studies either did not report how samples were selected for evaluation (Supplementary Table 3), 19 , 20 or reported that only samples which had sufficient residual volume and had been properly stored were selected. 18 Cradic et al and Zhen & Mangi et al…”
Section: The Performance Of Rrt-pcr Compared To Various Composite Refmentioning
confidence: 99%
“…In the absence of clinical trials and a gold standard for COVID-19 diagnosis, the clinical performance of SARS-CoV-2 assays is unclear. Anecdotal claims of poor NAAT performance exist in the lay press, and limited studies have shown variable performance of rapid POC tests ( Cradic et al, 2020 ; Harrington et al, 2020 ; Mitchell and George, 2020 ; Moore et al, 2020 ; Rhoads et al, 2020 ; Smithgall et al, 2020 ; Visseaux et al, 2020 ; Wolters et al, 2020 ; Zhen et al, 2020 ). As a surrogate for a gold standard, a composite reference standard (CRS) can be used to determine the consensus of comparable assays and identify outlier assays in terms of clinical performance ( Schiaffino et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%